TEACHING TRANSLATION: OBJECTIVES AND METHODS - Iryna Kobyakova; Svitlana Shvachko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The article is focused on the set of items: teaching translation, objectives, exercises and assignments (both word-centered and text-centered translation), translation analysis. The choice of the items is motivated by the dominant functions of transatology (nominative and communicative). The latter succeed in identification of adequate, congruent, equivalent translation. The article discusses the problems of professional validity, theoretical insertions, textocentric analysis. Gains, achievements, goals and perspective vistas are the highlights herein. The ways of translation adaptation have been outlined, among them are conceptualization, de-focusing, redundancy (language economy). The rendering of the original texts into target ones brings the diversity of the exercises and assignments what is the focus centre of the paper. The paper gives an opportunity to make translation analyses of the original and target texts. Semantic isotopy, textual non-linearity, self-organization, rhisomatic way of arranging textual cohesion and coherence, ramified architectonics and interpretation plurality remain actual, urgent, still unsolved problems in translatology. The major principles are manifested in conceptualization, de-focusing, expanse, redundancy (language economy) specific arrangement.